A Joint Autoethnography on Personnel Preparation Programs: Insights From Two MSIs - Acar, Serra; Matute-Chavarria, Monique; Wiegand, Sarah D.; Ku, Da Hei; Abo-Zena, Mona M.; Brayden-Calias, Katie; Hernandez, Anita (Topics in early childhood special education, 2025)
There is a growing interest in increasing the number of early interventionists and early childhood special education educators from racially, ethnically, and linguistically diverse backgrounds who provide services to infants and toddlers with disabilities and their families. However, higher education institutions often do not address the systemic barriers students from diverse backgrounds face in personnel preparation programs. In this study, we explored the recruitment and retention efforts of diverse students for personnel preparation programs and studied the sustainability of a diverse workforce and the unique role of minority-serving institutions (MSIs) in diversifying the field. We implemented collaborative autoethnography to highlight our lived experiences on recruitment, retention, and sustaining racially, ethnically, and linguistically diverse students from two different MSIs.